AKSEPTABILITAS BUBUK MULTI-ZAT-GIZI-MIKRO OLEH BALITA KELUARGA MISKIN DI JAKARTA UTARA - Nurfi Afriansyah; Hermina Hermina; Ema Luciasari; Yurista Permanasari; Noviati Fuada; Abas B. Jauhari (Persagi, 2009)
Acceptability of Multiple-Micronutrient Powders By Under-Fives of Poor Families In North Jakarta.Background: The final of three steps in developing the Indonesia Multiple-Micronutrient Powders (MMP) called TABURIA was to evaluate its effectiveness in improving the nutritional status of under-fives under programmatic setting. Together with execution of the final step, it was also necessary to conduct the subject's perception, satisfaction, and expectation toward TABURIA.Objectives: To find-out the acceptability of under-fives' mothers toward TABURIA.Methods: We assessed the acceptability of TABURIA for under-fives of poor families in North Jakarta. This under-fives beneficiaries of the MMP project participating in